2015
DOI: 10.18805/lr.v0iof.6781
|View full text |Cite
|
Sign up to set email alerts
|

Effect of weed management and sulphur on nutrient content and uptake by weeds and soybean

Abstract: A field experiment was undertaken to study the effect of weed management and sulphur nutrition on nutrient content and uptake by weeds and soybean during kharif 2009. The results revealed that application of two hoeing and weedings and imazethapyr 100 g/ha+ H&W at 40 DAS recorded maximum seed yield (1475 and 1395 kg/ha, respectively). Two H&W significantly reduced the weed growth and nutrient uptake by weeds, there by increased the nutrient (N, P and S) uptake by crop. Application of 40 kg S /ha significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
1
1
Order By: Relevance
“…Among herbicidal treatments, significantly higher nitrogen (1.245%), phosphorus (0.185%) and potassium (1.590%) content in the stalk of pigeon pea was observed in treatment T 14 over alone application of imidazolinones either applied PRE or POE. These results are in contrary with the findings of Dhaker et al (2015) who reported that weed management did not affects the nutrient content of seed and haulm of soybean.…”
Section: Nutrient Content In Pigeon Pea As Affected By Weed Control Measurescontrasting
confidence: 99%
“…Among herbicidal treatments, significantly higher nitrogen (1.245%), phosphorus (0.185%) and potassium (1.590%) content in the stalk of pigeon pea was observed in treatment T 14 over alone application of imidazolinones either applied PRE or POE. These results are in contrary with the findings of Dhaker et al (2015) who reported that weed management did not affects the nutrient content of seed and haulm of soybean.…”
Section: Nutrient Content In Pigeon Pea As Affected By Weed Control Measurescontrasting
confidence: 99%
“…The increase in seed and haulm yield with application of vermicompost might be due to better availability of nutrients in the soil, nutritional status of the crop and increased accumulation of photosynthates and their remobilization to reproductive parts of the plants, being the closest sink and hence, resulted in increased flowering, fruiting and seed formation. Thus, such results also corroborate with the findings of Singh and Singh (2005), Dubey et al (2012) and Dhaker et al (2015).…”
Section: Production Of Fenugreek (Trigonella Foenum-graecum) As Influenced By Weed Management Practices and Vermicompost Applicationsupporting
confidence: 91%
“…, respectively) and proved significantly superior to all the treatments (Table 2), except chlorimuron-ethyl 24 g + mechanical weeding (40 DAS). [19] also supported the findings. The crop under weed free plots attained lush growth due to elimination of weeds from inter and intra row spaces besides better aeration due to manipulation of surface soil and thus, more space, water, light and nutrients were available for the better growth and development, which resulted into superior yield attributes and development, and consequently the highest yield.…”
Section: Yield Attributes and Yieldsupporting
confidence: 77%